What have we learned? 10 years of current issues in methods and practice. Issue 24 (16th December 2020) - Lanke, Parijat; Nath, Papri
ABSTRACT: This paper has a two-fold purpose, first is to provide a review of the state of research published in the ' Current Issues in Method and Practice' (CIMP) section of the journal Current Issues in Tourism (CIT), and then to chalk out the overall conceptual structure of the journal during the last decade. This study combines a manual investigation with software-based analysis to answer the questions posed. The articles were manually identified for the CIMP section, while the data for conceptual structure analysis was accessed using Web of Science (WoS) database, resulting in a total of 50 papers from the CIMP section and 790 articles from WoS for the journal. Findings from the CIMP section, reveal that there is a clear movement towards introducing objective measures such as electromyography and wavelet analysis, borrowed from natural sciences, whereas overall the studies in current issues in tourism are leaning towards individual-level analysis.